(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aims to assess the impact of liquid waste (petroleum hydrocarbons) from car wash and oil change stations in the Al-Ajilat area on groundwater quality for various uses. Eight groundwater samples were collected and analyzed from wells located within the immediate geographical range of the stations. Tests were conducted using a HORIBA OCMA-500 instrument to determine the total hydrocarbon (TPH) concentrations. The results showed that all studied sites suffered from hydrocarbon pollution exceeding safe limits, with concentrations ranging from 0.5 to 17.3 mg/L. The comparative analysis revealed that stations attached to fuel stations recorded the highest pollution levels at a concentration of 17.3 mg/L, which is several times higher than the concentrations recorded at stations that only wash and change oil.